Clinical Outcome of Patients With High-Risk Endometrial Carcinoma After Treatment With Chemotherapy Only. Issue 9 (1st November 2018) - Smogeli, Elisabeth; Cvancarova, Milada; Wang, Yun; Davidson, Ben; Kristensen, Gunnar; Lindemann, Kristina
Abstract : Objectives: Adjuvant treatment of high-risk endometrial cancer (EC) is still controversial. Several studies have tried to clarify the best treatment strategy, and guidelines have been made, but no study to date has shown a survival benefit for radiation over chemotherapy. We aimed to evaluate the outcome of high-risk EC patients treated with adjuvant chemotherapy only in a population where the routine administration of adjuvant radiotherapy was omitted. Methods: This is a retrospective study including 230 EC patients with International Federation of Gynecology and Obstetrics stage I type II, stage Ib type I/G3, stage II, and IIIc treated at Oslo University Hospital between 2005 and 2012. Standard treatment was hysterectomy, bilateral salpingo-oophorectomy and at least pelvic lymphadenectomy followed by adjuvant chemotherapy. Results: Of the 230 high-risk patients, standard treatment was given to 146 patients (63.5%): 60 patients in stage I, 10 patients in stage II, and 76 patients in stage IIIc. Only 10% of patients with stage I disease relapsed, with 3.3% locoregional relapses and 6.7% distant relapses. Recurrence rate in stage IIIc was 39.5%, with 7.9% isolated vaginal and 31.6% distant relapses. The 3-year disease-free survival was 92% for stage I, 80% for stage II, and 60% for stage IIIc disease. In the total population, 55 patients had International Federation of Gynecology and Obstetrics stage Ia, 43 Ib, 42 stage II, and 90 stage IIIc disease. Recurrence rate in the total population was 29.6%, with 9.6% isolated vaginal recurrences, 1.7% recurrences located in the pelvis, and 18.3% distant recurrences. Conclusions: Patients with high-risk EC have acceptable vaginal/pelvic control rates after adjuvant chemotherapy. However, prognosis remains poor for patients with stage IIIc disease, also after chemotherapy.